2023
DOI: 10.1021/acsomega.3c06806
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fatty Acid Modification on the Anticancer Activity of the Antimicrobial Peptide Figainin 1

Zhenbin Han,
Dongmei Feng,
Wenxuan Wang
et al.

Abstract: Antimicrobial peptides derived from the skin secretions of amphibians have made important progress in tumor therapy due to their unique mechanism of destroying cell membranes. Figainin 1 (F1) is an 18-amino acid antimicrobial peptide from the skin secretions of Boana raniceps frogs. In a previous study, F1 was shown to inhibit cancer cell proliferation. F1 is composed entirely of natural amino acids; therefore, it is easily degraded by a variety of proteases, resulting in poor stability and a short half-life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Our previous computational estimations regarding their properties indicated a higher lipophilicity (cLogP) and lower solubility for RUT-O and RUT-L compared to their parent compound RUT, which is in agreement with the data presented in the literature [10]. A similar correlation between the modification of compounds with fatty acids, their hydrophobicity, and ability to disrupt cell membranes was found in a study conducted by Han and collaborators [35]. Viskupicova et al showed that the conjugation of RUT with fatty acids leads to compounds with increased hydrophobicity and solubility in fats, and presented several works indicating that RUT lipophilic derivatives present better bioavailability and crossing through biological membranes [36].…”
Section: Discussionsupporting
confidence: 90%
“…Our previous computational estimations regarding their properties indicated a higher lipophilicity (cLogP) and lower solubility for RUT-O and RUT-L compared to their parent compound RUT, which is in agreement with the data presented in the literature [10]. A similar correlation between the modification of compounds with fatty acids, their hydrophobicity, and ability to disrupt cell membranes was found in a study conducted by Han and collaborators [35]. Viskupicova et al showed that the conjugation of RUT with fatty acids leads to compounds with increased hydrophobicity and solubility in fats, and presented several works indicating that RUT lipophilic derivatives present better bioavailability and crossing through biological membranes [36].…”
Section: Discussionsupporting
confidence: 90%